Circulating endothelial cells and tumor blood volume as predictors in lung cancer. Issue 4 (9th February 2013) - Wang, Jing; Xiao, Jianyu; Wei, Xiyin; Wang, Liuchun; Lin, Li; Liu, Zhujun; Wang, Xinyue; Sun, Baocun; Li, Kai
<x xml:space="preserve">Abstract</x> The current criteria for evaluating antiangiogenic efficacy is insufficient as tumor shrinkage occurs after blood perfusion decreases. Tumor blood volume (BV) in computed tomography perfusion imaging and circulating endothelial cells (CEC) might predict the status of angiogenesis. The present study aimed to validate their representation as feasible predictors in non‐small‐cell lung carcinoma (NSCLC). A total of 74 patients was categorized randomly into two arms undergoing regimens of vinorelbine and cisplatin (Navelbine and platinum [NP]) with rh‐endostatin or single NP. The response rate, perfusion imaging indexes and activated CEC (aCEC) during treatment were recorded. Progression‐free survival (PFS) was determined through follow up. Correlations among the above indicators, response and PFS were analyzed: aCEC increased significantly in cases of progressive disease after single NP chemotherapy (P = 0.024). Tumor BV decreased significantly in cases with a clinical benefit in the combined arm (P = 0.026), whereas inverse correlations existed between ∆aCEC (post‐therapeutic value minus the pre‐therapeutic value) and PFS (P = 0.005) and between ∆BV and PFS (P = 0.044); a positive correlation existed between ∆aCEC and ∆BV. Therefore, both aCEC and tumor BV can serve as predictors, and detection of both indicators can help evaluate the chemo‐antiangiogenic efficacy in NSCLC more accurately.